Evaluation of energy and exergy analysis of apple juice production and waste valorization processes - Cabuk Kok, Duygu; Genc, Seda; Goksungur, Yekta (Frontiers in Sustainable Food Systems, 2025)
Apple juice production is an essential part of the global beverage industry with notable implications for sustainable development. However, the process generates significant exergy destruction and waste by-products. A systematic evaluation of process efficiency and valorization of by-products is necessary to support resource optimization and sustainability. This study applied exergy analysis to assess the sustainability of apple juice production processes. Two common methods were examined: aseptic filling and glass bottle filling. Exergy destruction, energy efficiency, and exergy efficiency were calculated for each stage. Additionally, the by-product apple pomace was processed into value-added products (apple jam and dietary fiber) to evaluate the impact on overall system efficiency. Sankey-Grassmann diagrams were used to visualize exergy flows. The total exergy destruction was 608.15 kW for aseptic filling and 538.27 kW for glass bottle filling. Energy efficiencies were determined as 80.8% and 98.8%, while exergy efficiencies were 58.9% and 59.9%, respectively. The mixing tank caused the highest exergy destruction (307.1 kW), followed by the second pressing stage (80.82 kW) and the cooling-1 stage (75.97 kW). When apple pomace was valorized, the exergy efficiency of aseptic filling increased to 82.5% (jam) and 72.4% (dietary fiber), while glass bottle filling improved to 83.5% (jam) and 73.4% (dietary fiber). The findings highlight the crucial role of chemical exergy in evaluating process sustainability. Valorization of apple pomace into jam and dietary fiber significantly improves exergy efficiency while reducing waste. This approach enhances resource utilization, decreases environmental burden, and supports the transition toward a more sustainable beverage production model.